Effect of hydration with or without n-acetylcysteine on contrast induced nephropathy in patients undergoing coronary angiography and percutaneous coronary intervention - Awal, A; Ahsan, SA; Siddique, MA; Banerjee, S; Hasan, MI; Zaman, SM; Arzu, J; Subedi, B (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Apr;20(2): 264-269 The abstract of this article is available on the PubMed website